ANALISIS PENDAPATAN USAHATANI TOMAT APEL DI DESA TEMPOK KECAMA-TAN TOMPASO KABUPATEN MINAHASA SELATAN (Analysis of Apple Tomato Business Income in Tempok Village, Tompaso District, South Minahasa Regency) - Elsa E. Lampus; Juliana R. Mandei; Gene H. M. Kapantow (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
This study aims to analyze the income of Apple Tomato farming in Tempok Village, Tompaso District, Minahasa Regency. The data used in this research were primary data and secondary data. Primary data were obtained from direct interviews with farmers using a questionnaire. The number of respondents was 20 apple tomato farmers who were randomly selected from 2 Jagas in the village. The sample was divided into two categories, namely farmers who had their own land and farmers who rented land.The results showed that if only taking into account explicit costs, the average income per hectare of apple tomato farming in Tempok Village, Tompaso District for farmers who had their own land was IDR 22,989,297, while the income per hectare of farmers who rent land was IDR 11,156,570. However, if implicit costs were taken into account, the income of farmers who own their own land was only IDR 17,155,963/Ha, while the income of farmers who rent landÂ  was IDR 4,071,504/Ha.